Re: How to find one expression in terms of another expression?

*To*: mathgroup at smc.vnet.net*Subject*: [mg119765] Re: How to find one expression in terms of another expression?*From*: Jacare Omoplata <walkeystalkey at gmail.com>*Date*: Tue, 21 Jun 2011 05:52:21 -0400 (EDT)*References*: <itm0of$143$1@smc.vnet.net> <itolk6$er6$1@smc.vnet.net>

Thanks for this answer. On Jun 20, 7:37 pm, Ray Koopman <koop... at sfu.ca> wrote: > > Omit 'dt = t2 - t1'. Otherwise, every time you write 'dt' > it will be replaced by 't2 - t1'. Here is all you need: > > In[1]:= > T1 = (t1 - ((u x1)/c^2))/Sqrt[1 - (u^2/c^2)]; > T2 = (t2 - ((u x2)/c^2))/Sqrt[1 - (u^2/c^2)]; > dT = Simplify[T2 - T1] /. t2 - t1 -> dt > {b,a} = CoefficientList[dT,dt] > > Out[3]= (c^2*dt + u*(x1 - x2))/(c^2*Sqrt[1 - u^2/c^2]) > > Out[4]= {(u*(x1 - x2))/(c^2*Sqrt[1 - u^2/c^2]), 1/Sqrt[1 - u^2/c^2]}